Peningkatan Kesejahteraan Ekonomi Masyarakat Desa Waruduwur Kecamatan Mundu Melalui Pemberdayaan Potensi Lokal - Afinanda, Adinda Salwa; Nurajizah, Fiqih; Amaliyah, Linda; Maufuroh, Najihah; Serliana, Neneng; Fauziah, Salma Nur (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This study examines the level of economic well-being of thepeople of Waruduwur Village, Mundu District, which is closely relatedto the utilization of local potential. Waruduwur Village is known for itspotential in fisheries, seafood trade, and micro, small, and mediumenterprises (MSMEs). This research was conducted using observation,interviews, and questionnaires with the community and villageofficials. The results show that the level of community well-being varies;most people depend on seafood but face challenges in marketing andlimited access to capital. Community empowerment efforts throughskills training, strengthening economic institutions, and governmentsupport can improve their well-being. Thus, this research makes animportant contribution to village development strategies based onlocal potential.